2021
DOI: 10.1039/d1cc01354h
|View full text |Cite
|
Sign up to set email alerts
|

Electron doping of single-walled carbon nanotubes using pyridine-boryl radicals

Abstract: Electron doping of single-walled carbon nanotubes with pyridine-boryl radicals proceeds by electron transfer from the radicals to SWCNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Notably, the N 1s was observed in the pristine SWCNTs due to the residual NMP, and the N content of the three composites originated from not only the residue of the NMP but also the amino acids. Consequently, the changes of N 1s peaks can reflect the intermolecular interactions between the three basic amino acids and SWCNTs Figure b–e showed N 1s spectra of the pristine SWCNTs, SWCNT/His, SWCNT/Lys, and SWCNT/Arg films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the N 1s was observed in the pristine SWCNTs due to the residual NMP, and the N content of the three composites originated from not only the residue of the NMP but also the amino acids. Consequently, the changes of N 1s peaks can reflect the intermolecular interactions between the three basic amino acids and SWCNTs Figure b–e showed N 1s spectra of the pristine SWCNTs, SWCNT/His, SWCNT/Lys, and SWCNT/Arg films.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the changes of N 1s peaks can reflect the intermolecular interactions between the three basic amino acids and SWCNTs. 42 Figure 6b−e showed N 1s spectra of the pristine SWCNTs, SWCNT/His, SWCNT/Lys, and SWCNT/Arg films. The binding energy of N 1s is located at around 400 eV for all films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2A). 30 After drying the SWCNT lms, the Seebeck coe cient and electrical conductivity of the doped SWCNT lms were evaluated. In this study, pyridine derivatives 4-CNpy, 4-Phpy, 4-OMepy, 4pyridinecarboxylic acid (4-COOHpy), 4-octylpyridine (4-C 8 H 17 py), and 2,4,6-triphenylpyridine (2,4,6-Triphpy) were investigated.…”
Section: Electron Doping Of Swcnt Using Boryl Radicalsmentioning
confidence: 99%
“…1B). 30 In this system, the reaction between bis(pinacolato)diboron (B 2 pin 2 ) and 4-cyanopyridine (4-CNpy) generated a pyridineligated boryl radical, (4-CNpy)Bpin • , by the homolytic cleavage of the B-B bond in B 2 pin 2 via the coordination of 4-CNpy to boron atoms. 29 Moreover, the experimental and theoretical analyses demonstrated that the electron transfer from (4-CNpy)Bpin • to SWCNTs formed a cation, (4-CNpy)Bpin + , on the SWCNT surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, highly reactive species such as organic radicals have been used for efficient n-type doping. Fujigaya and colleagues utilized in situ generated pyridine (py)-boryl radicals to n-dope SWCNTs [38].…”
Section: Hydrogen Hydride and Radical Transfer-type Dopantsmentioning
confidence: 99%